Electron-beam sintering of an Al2O3 / Ti composite using a forevacuum plasma-cathode electron source. Issue 14 (1st October 2020) - Klimov, A.S.; Bakeev, I. Yu; Oks, E.M.; Zenin, A.A.
Abstract: We present the results of electron-beam sintering of composite ceramic compacts based on alumina and titanium powders. The electron beam was generated by a plasma-cathode electron source at elevated pressure values of the fore-vacuum range. We have studied the effect of the pressed compact thickness on the sintered sample parameters. It has been established that the pressed thickness significantly affects the uniformity of parameters. The samples with the most uniform parameters were obtained for thickness values below 4 mm. At a greater thickness, the parameter non-uniformity increases considerably due to outgassing from the surface of the sintered compacts.